Consumption and foraging behaviors for common stimulants (nicotine, caffeine). Issue 1 (2nd January 2016) - Phillips, James G.; Currie, Jonathan; Ogeil, Rowan P.
ABSTRACT: Models are needed to understand the emerging capability to track consumers' movements. Therefore, we examined the use of legal and readily available stimulants that vary in their addictive potential (nicotine, caffeine). One hundred sixty-six participants answered the Kessler Psychological Distress Scale (K10), the Severity of Dependence Scale for nicotine and caffeine, and reported the number of times and locations stimulants were purchased and used. On average, nicotine dependent individuals made their purchases from 2 locations, while caffeine dependent individuals consumed caffeine at 2 locations, but some people exhibited a greater range and intensity of use. Stimulant foraging behavior could be described by power laws, and is exacerbated by dependency. The finding has implications for attempts to control substance use.